PERSEPSI SISWA TERHADAP MODEL PEMBELAJARAN KONSTRUKTIVISME DALAM MENINGKATKAN KEMAMPUAN MAHARAH KITABAH - Muhyiddin, Imam Irsyad; Syuhadak, Syuhadak; Rochman, Taufiqur (Center for Research and Community Service (LPPM) University of Abulyatama, 2025)
This study aims to examine students' perceptions of the constructivism learning model in improving mahara kitabah skills at MAN 1 Indragiri Hilir. This research uses a qualitative approach with a phenomenological study method. The research subjects were grade XI students who participated in learning maharah kitabah with constructivism model. Data were collected through in-depth interviews, participatory observation, and documentation of student writing. Data analysis was conducted using thematic analysis technique. The results showed that students have a positive perception of constructivism learning which makes learning more interactive, collaborative, and meaningful. This learning model is proven to be able to improve students' Arabic writing skills, especially in sentence structure, vocabulary, and fluency in conveying ideas. The obstacles faced are shyness during presentation and difficulty expressing written ideas. This study recommends teachers to develop inclusive and supportive learning methods to overcome these obstacles and improve the effectiveness of mahara kitabah learning.